The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pntd.0005771
|View full text |Cite
|
Sign up to set email alerts
|

The disease burden of human cystic echinococcosis based on HDRs from 2001 to 2014 in Italy

Abstract: BackgroundCystic echinococcosis (CE) is an important neglected zoonotic parasitic infection belonging to the subgroup of seven Neglected Zoonotic Disease (NZDs) included in the World Health Organization’s official list of 18 Neglected Tropical Diseases (NTDs). CE causes serious global human health concerns and leads to significant economic losses arising from the costs of medical treatment, morbidity, life impairments and fatality rates in human cases. Moreover, CE is endemic in several Italian Regions. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…It should be noted that these three studies showed a negative trend in time in the number of hospitalisations. More recently, an extended study conducted in Italy (which is currently not reporting any human CE cases to the EU annual zoonoses monitoring data collection) identified 21,050 hospital discharge records with CE diagnosis from 2001 to 2014 related to 12,619 patients (Piseddu et al., ). The median of CE hospitalisations per year in Italy was 848, which is equal to the total number of CE and AE cases reported by all the MS in the EU annual zoonoses monitoring data collection.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that these three studies showed a negative trend in time in the number of hospitalisations. More recently, an extended study conducted in Italy (which is currently not reporting any human CE cases to the EU annual zoonoses monitoring data collection) identified 21,050 hospital discharge records with CE diagnosis from 2001 to 2014 related to 12,619 patients (Piseddu et al., ). The median of CE hospitalisations per year in Italy was 848, which is equal to the total number of CE and AE cases reported by all the MS in the EU annual zoonoses monitoring data collection.…”
Section: Discussionmentioning
confidence: 99%
“…At global level, Budke and colleagues [3] estimated a human burden of around 1 million Disability-Adjusted Life Years (DALYs) and 760 million US$ losses due to human infection (accounting for underreporting), and annual livestock production losses of at least US$ 140 million. For what concerns Europe, in Italy, based on Hospital Discharge Records (HDR), Piseddu and colleagues [4] estimated a financial burden due to human CE of around € 53 million in 2001-2014, with a national average economic burden of € 4 million per year. In Spain, Benner and colleagues [5] estimated, for the year 2005, and overall economic loss due to human and livestock CE of about € 150 million, of which about 130 million were human-associated and about 16 million animal-associated.…”
Section: Introductionmentioning
confidence: 99%
“…and Italy and the Mediterranean countries are considered endemic . In Italy, the prevalence in 2014, estimated on hospital discharge records, is up to 1.06/100 000 inhabitants/year, but it is expected that these data are underestimated as outpatients or asymptomatic patients are not included in the analysis . CE diagnosis and clinical management are based on ultrasound (US).…”
Section: Introductionmentioning
confidence: 99%